2012
DOI: 10.1088/0957-4484/23/25/255301
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of high-density In3Sb1Te2phase change nanoarray on glass-fabric reinforced flexible substrate

Abstract: Mushroom-shaped phase change memory (PCM) consisting of a Cr/In(3)Sb(1)Te(2) (IST)/TiN (bottom electrode) nanoarray was fabricated via block copolymer lithography and single-step dry etching with a gas mixture of Ar/Cl(2). The process was performed on a high performance transparent glass-fabric reinforced composite film (GFR Hybrimer) suitable for use as a novel substrate for flexible devices. The use of GFR Hybrimer with low thermal expansion and flat surfaces enabled successful nanoscale patterning of functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Phase change random access memory (PCRAM) are characterized by high transition speeds, for instance, Ge2Sb2Te5-based flexible PCRAM with 30 ns pulse for switching, ultra-high integration densities of up to terabits per square inch were achieved due to highly localized regions of phase change [21], [22]. However, lower yield of 66% and endurance of 1000 bending cycles for PCRAM are worth examining concerns restricting its practical implementation [23].…”
Section: B Memory Management Modulementioning
confidence: 99%
“…Phase change random access memory (PCRAM) are characterized by high transition speeds, for instance, Ge2Sb2Te5-based flexible PCRAM with 30 ns pulse for switching, ultra-high integration densities of up to terabits per square inch were achieved due to highly localized regions of phase change [21], [22]. However, lower yield of 66% and endurance of 1000 bending cycles for PCRAM are worth examining concerns restricting its practical implementation [23].…”
Section: B Memory Management Modulementioning
confidence: 99%
“…Another advantage of PCRAM is its highly localized regions of phase change that enables ultra-high integration densities. In 2011, Hong et al also reported phase-change nano-pillar devices with the potential of reaching up to tera bit/squared inch densities on flexible substrates [253] and the following year, Yoon et al demonstrated a 176 Gbit/square inch PCRAM [254], the highest reported density on a flexible substrate. The highest reported bending cycles endurance (1000 bending cycles) and yield (66%) for flexible PCRAM was reported by Mun et al, in 2015 [255].…”
Section: Flexible Pcrammentioning
confidence: 99%
“…NVMs can retain information even when no power is supplied. There are five major classes of NVMs [70]: resistive RAM (ReRAM) also referred to as memristor [143][144][145][146], ferroelectric RAM (FeRAM), [147] magnetic RAM (MRAM) [148,149], phase change RAM (PCRAM) [150,151], and flash memory (floating gate (FG) and charge trapping (CT)) [80,152,153]. Other technologies, such as nano-electromechanical (NEM) NVMs [154,155] and molecular based NVMs [156] exist but they are not mainstream.…”
Section: Nvm Operational Principlesmentioning
confidence: 99%
“…21 Furthermore, previously reported flexible phase-change memories, composed of nanodot/wire arrays, are not practical solutions for commercialization from the viewpoints of device reliability, nanomaterials alignment, and interconnection issues. 23,24 Block copolymer (BCP) self-assembly, a spontaneous organization phenomenon of two mutually immiscible polymer blocks, can achieve regularly ordered arrays with sub-20 nm features. 25À32 Self-assembly of BCPs has shown promising potential to complement photolithography because of B its low-cost process, excellent resolution, scalability, and applicability to the conventional CMOS technology.…”
mentioning
confidence: 99%
“…Although a straightforward way to reduce writing current is to further decrease the contact area between the heater layer and the phase-change material, conventional photon-based nanolithography techniques cannot easily be applied on rough flexible substrates due to limit of high-precision focusing and inaccuracy of multilevel registration . Furthermore, previously reported flexible phase-change memories, composed of nanodot/wire arrays, are not practical solutions for commercialization from the viewpoints of device reliability, nanomaterials alignment, and interconnection issues. , …”
mentioning
confidence: 99%